Long-term treatment with rituximab in severe juvenile idiopathic arthritis-associated uveitis. Issue 6 (22nd September 2015) - Miserocchi, Elisabetta; Modorati, Giulio; Berchicci, Luigi; Pontikaki, Irene; Meroni, Pierluigi; Gerloni, Valeria
Abstract : Background/aims: To evaluate retrospectively the long-term efficacy of rituximab in patients with severe juvenile idiopathic arthritis (JIA)-associated uveitis. Methods: Eight patients (15 eyes) with severe and longstanding JIA uveitis, who had an inadequate response in controlling uveitis to one or more biologic agents including tumour necrosis factor blockers and abatacept, received rituximab therapy. Rituximab was given at a dose of 1000 mg per infusion on days 1 and 15 and then every 6 months. Clinical responses to treatment, including decrease in uveitis activity, visual acuity changes, reduction of concomitant local and systemic corticosteroid and/or immunosuppressants, and occurrence of adverse events, were assessed. Results: Eight patients with a mean±SD age of 22.8±5.5 years were treated. The mean ocular disease duration was 17.7 years; the mean±SD follow-up time on rituximab was 44.75±4.9 months; and the mean number of rituximab infusions received was 8.75 (range 6–12). All patients achieved complete control of uveitis, but in two patients rituximab was discontinued due to inefficacy in treating arthritis. The decrease in uveitis activity was evident 4–5 months after the first infusion. Systemic corticosteroids and immunosuppressants used in association with rituximab were discontinued in five patients at the end of follow-up. None of the patients experienced visual worsening during the follow-up. No drug-related complications were encountered. Conclusions: Rituximab may be a promising effective treatment option for refractory uveitis associated with JIA leading to long-term quiescence of uveitis, particularly for patients who have not previously responded to other biologic therapies.